2014
DOI: 10.1177/1477153514539781
|View full text |Cite
|
Sign up to set email alerts
|

The influence of luminance, observation duration and procedure on the recognition of pedestrians’ faces

Abstract: Past studies carried out to determine whether the spectral power distribution (SPD) of a lamp affects facial recognition led to mixed results, and one reason for this could be that different studies presented different levels of task difficulty, this being a function of target size, observation duration and type of procedure. This article presents two facial recognition experiments carried out using matching and identification procedures to explore task difficulty as defined by observation duration and target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…[6][7][8][9][10][11][12] Further studies have sought judgements when targets are presented at one or more fixed distances. [13][14][15][16][17][18][19][20] The stop-distance procedure reveals the distance at which a task could be completed, but does not reveal whether that distance approximates that at which it is desirable for pedestrians after dark. Experiments seeking judgements at fixed distances may exhibit better ecological validity but only if the distances used in trials include (or bracket) that which approximates pedestrians' desired distance for evaluating other people.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Further studies have sought judgements when targets are presented at one or more fixed distances. [13][14][15][16][17][18][19][20] The stop-distance procedure reveals the distance at which a task could be completed, but does not reveal whether that distance approximates that at which it is desirable for pedestrians after dark. Experiments seeking judgements at fixed distances may exhibit better ecological validity but only if the distances used in trials include (or bracket) that which approximates pedestrians' desired distance for evaluating other people.…”
Section: Introductionmentioning
confidence: 99%
“…The crime prevention lighting aims at reducing crime occurrence through lighting design [3][4]. The main purpose using it in residential area is to provide security and comfort environment for people [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, concluded that there is a significant effect of SPD 137,160 and these data contributed to an assumed benefit of better colour quality in revised guidance. 68 Subsequent research first examined methodology, proposing that different procedures may lead to different conclusions, 161,162 that facial emotion recognition from expression is a more suitable task than identify recognition, [163][164][165] that a brief duration of 500 ms better resembles typical behaviour than does continuous observation, 166,167 and that the stop-distance approach used in many studies may not lead to the same conclusions as evaluations made at the desirable observation distance of 15 m. 166,167 In studies carried out using facial emotion recognition, SPD is not suggested to be a critical parameter. [168][169][170][171] One question still to be resolved is whether a measure of vertical illuminance is needed to characterise this task or whether it is safe to assume that horizontal illuminance at the road surface is sufficient.…”
Section: Comparing Approachesmentioning
confidence: 99%